Evaluasi Kebijakan Kepala Sekolah dalam Mewujudkan Visi dan Misi di MAS Pab 1 Sampali - Mesiono Mesiono; Inom Nasution; Eliza Putri (STIKes Ibnu Sina Ajibarang, 2024)
The aim of this research is to find out: the principal's policy planning in realizing the vision and mission, evaluation of the principal's policies in realizing the vision and mission. The research methodology uses qualitative research methods, the approach used in this research uses observation, interviews and documentation. The informant in this research was the principal at the school. Data analysis in this research uses data reduction, data presentation and refinement. The data validity technique in this research uses data credibility, transferability, dependability and confirmability tests. Based on the research that the researcher has carried out, which has been implemented, the evaluation of the school principal's policy can be seen from the planning/formulation process which has been implemented well.